CARCASS CHARACTERISTICS OF LARGE WHITE YORKSHIRE GROWER PIGS MAINTAINED UNDER ROOF INSULATION AND WATER FOGGING SYSTEM DURING SUMMER SEASON - S. Priscilla Rani; Thanga. Thamil Vanan; T. Sivakumar; D. Balasubramanyam; A. Thennarasu (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was carried out to assess the effect of heat stress amelioration practices such as roof insulation and water fogging on the carcass characteristics of Large White Yorkshire grower pigs in summer season. Forty numbers of weaned pigs were assigned to five treatment groups randomly. It was observed that the groups maintained under insulated roofing with 10 and 5 minutes fogging had significantly (P